Factorize :

Algebra Level 1

Factorize the expression

x 2 + x 12. x^2 + x - 12.

( x + 4 ) ( x 3 ) ( x + 4 ) ( x - 3) ( x + 6 ) ( x 4 ) ( x + 6 ) ( x - 4 ) ( x 7 ) ( x 5 ) ( x - 7 ) ( x - 5 ) ( x + 5 ) ( x 3 ) ( x + 5 ) ( x - 3)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Munem Shahriar
May 13, 2017

x² + x - 12

= x² - 4x + 3x -12

= x( x - 4 ) - 3 ( x - 4 )

= ( x - 3 ) ( x - 4 ) Answer

Jack Rawlin
Dec 22, 2014

Since ( a x + b ) ( c x + d ) = a c x 2 + a d x + c b x + b d (ax + b)(cx + d) = acx^2 + adx + cbx + bd

a c x 2 = x 2 , a d x + c b x = x acx^2 = x^2, adx + cbx = x and b d = 12 bd = -12

a c x 2 = x 2 a c = 1 acx^2 = x^2 \Rightarrow ac = 1

If something factorises it means that a a and c c are both integers which means that a = 1 a = 1 and c = 1 c = 1

a d x + c b x = x a d + c b = 1 adx + cbx = x \Rightarrow ad + cb = 1

Since a , c = 1 a, c = 1

a d + c b = 1 d + b = 1 ad + cb = 1 \Rightarrow d + b = 1

Rearrange d + b = 1 d + b = 1 to get an equation for b b

b = 1 d b = 1 - d

Next substitute that equation into b d = 12 bd = -12

( 1 d ) d = 12 (1 - d)d = -12

The expand and re-arrange

d d 2 = 12 d 2 + d + 12 = 0 d 2 d 12 = 0 d - d^2 = -12 \Rightarrow -d^2 + d + 12 = 0 \Rightarrow d^2 - d - 12 = 0

Since it's equal to zero we can use the quadratic formula

d = 1 ± 1 4 ( 1 ) ( 12 ) 2 d = \frac {1 \pm \sqrt {1 - 4(1)(-12)}}{2}

d = 1 ± 7 2 d = \frac {1 \pm 7}{2}

d = 4 , d = 6 d = 4, d = -6

Put these two values back into the equations, we'll start with d = 6 d = -6

b = 1 ( 6 ) b = 1 + 6 = 7 b = 1 - (-6) \Rightarrow b = 1 + 6 = 7

b ( 6 ) = 12 6 b = 12 b = 2 b(-6) = -12 \Rightarrow -6b = -12 \Rightarrow b = 2

As you can see d 6 d \neq -6

So d = 4 d = 4

b = 1 ( 4 ) = 3 b = 1 - (4) = -3

b ( 4 ) = 12 b = 3 b(4) = -12 \Rightarrow b = -3

So putting the values back into the original equation gives us

( x + 4 ) ( x 3 ) (x + 4)(x - 3)

Ashish Menon
May 28, 2016

Just obsever, 1 should be the sum of the roots and -12 should be yheir product. Out of the option only ( x + 4 ) ( x 3 ) \color{#69047E}{\boxed{(x + 4)(x - 3)}} satisfies this condition.

Iqrar Raza
Dec 18, 2014

since x=4 x-3 x, so,
x^2+x-12 =>
x^2+4 x-3 x-12 =>
x (x+4)-3 (x+4),
taking commen (x-4),
(x+4)*(x-3)




Rahul Saha
Aug 27, 2014

12 = 4 3 -12=4*-3 and the result follows.

You forgot the minus in front of the 12 Rahul

Abdur Rehman Zahid - 6 years, 5 months ago
Rifath Rahman
Aug 22, 2014

x^2+x-12=x^2+4x-3x-12=x(x+4)-3(x+4)=(x+4)(x-3)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...